Employee perceivedness towards the importance of workplace support system in reducing anxiety level among workers with cancer in Jordan - Abu Shreea, Abdel Rahman Aref Ali (2022)
This study is aimed to determine the prevalence of anxiety disorder among workers with cancer in the Jordanian population and its relationship with a workplace support system and work-related issues. To attain this aim, a cross-sectional study was conducted at the King Husain Cancer Centre (KHCC) in Amman, Jordan. A proportional sampling technique was used to obtain the sample population of (354) workers with cancer. The data were collected by self-administered Generalized Anxiety Disorder (GAD-7), and newly developed work-related issues and work support system questionnaires. To analyze the data, SPSS version 25 and AMOS version 25 were used. A response rate of 100% were obtained from the participants. Prevalence of anxiety disorder among workers with cancer was recorded at 20.8%, with male (23.1%) having the higher prevalence rate than female (17.3%) workers with cancers. A significant and a strong positive correlation between anxiety disorder and age rank (r = 1, p < 0.032) and anxiety disorder with age (r = 0.492, p < 0.037) were observed in this population. The logistic regression model was statistically significant, χ2(4.480) = 37, p < .0001. The model explained 30.8% (Nagelkerke R2) of the variance in anxiety disorder and correctly classified 76.3% of cases. Interestingly, female respondents were more likely to suffer from anxiety (AOR 2.448, 95% CI 0.371 to 1.118) than their male counterparts. In respect of the educated individuals, particularly the holder with a bachelor degree are 5.660 times more likely to suffer from anxiety (AOR 5.660, 95% CI 0.060 to 0.821); widowed/divorced respondents are more likely to suffer from anxiety (8.858) times the married respondents (AOR 8.858, 95% CI 0.072 to 34.396). There is a high prevalence of anxiety disorder among workers with cancer in Jordan. Predictors of anxiety among workers with cancer were also identified in this report. The study found that the government and the ministry of health should improve their management and intervention to avoid adding more deteriorating diseases to the workers with cancer. The study highlighted the importance of improving return to work theory for cancer employee. The study articulates the importance of relating workplace support system with mental health. The study recommends organizations to establish support programs to help employees manage their anxiety risks. The study took place at King Husain Cancer Centre (KHCC) in Amman, Jordan. The primary outcome of the study was that there is a significant difference in the workplace support system, work-related issues, and generalized anxiety disorder according to demographic information (age, gender, marital status, education, and job role). As for the secondary outcome was that the levels of anxiety among workers varied among the workers due to gender, educational, and job title. This study also presents implications that managing Jordan's workplace anxiety level for employee's resolve workplace issues and create a workplace support system is critical and bound to have practical implications in managing anxiety at the workplace.